La imagen polimórfica de Alejandro Magno desde la Antigüedad latina al Medievo hispánico: edición y estudio de las fuentes de un desatendido Libro de Alexandre prosificado - Saquero Suárez-somonte, Pilar; González Rolán, Tomás (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
If it is possible to talk about a true Golden Age referred to the subject of Alexander the Great, it would be the XIIIth century. At that moment, Two branches or tendencies take place on Spanish soil: the Western-European, represented by the Libro de Alexandre, and the Eastern-Islamic, which is very noticeable, together with the former, in the General Estoria by Alphonso X the Wise. An abridged and changed to prose Libro de Alexandre, whose sources have been analysed in detail, is related with the poem of the Mester de Clerecía, and probably also with the translating task of the Alphonsine writers.